High-stability porous hydroxyapatite microspheres as well as preparation method and application thereof

Porous hydroxyapatite microspheres are formed by self-assembly of nano-scale hydroxyapatite particles, which solves the problems of sharp microsphere structure and poor histocompatibility in the prior art, and achieves high stability and porous microspheres, which are suitable for a variety of biomedical applications.

CN119591066APending Publication Date: 2025-03-11SHANGHAI MOYANG BIOTECHNOLOGY CO LTD

Patent Information

Application Number
CN202411884001.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the prior art, the microstructure of hydroxyapatite microspheres is relatively sharp, has poor histocompatibility, and does not have a porous structure, which leads to an inflammatory response after in vivo injection, which is not conducive to the regulation of drug load and degradation time.

Method used

Self-assembled to form highly stable porous hydroxyapatite microspheres by nanoscale hydroxyapatite particles driven by thermodynamic behavior of reduced excess surface free energy. The microspheres have rough surfaces, nano- to micro-size particle sizes and nano-sized pore structures. Microspheres of different particle sizes and porosity can be obtained by adjusting production process parameters.

Benefits of technology

The problems of sharp microsphere structure, poor histocompatibility and non-porous structure in the prior art have been overcome. The prepared porous hydroxyapatite microspheres have high stability and good biocompatibility, and are suitable for applications in mineralization, bone tissue repair, drug sustained release carriers and tissue engineering scaffolds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591066A_ABST
    Figure CN119591066A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biomedical materials, and discloses a high-stability porous hydroxyapatite microsphere as well as a preparation method and application thereof, and the porous hydroxyapatite microsphere is formed by self-assembling nano-scale hydroxyapatite particles under the driving of a thermodynamic behavior of reducing excess surface free energy; the porous hydroxyapatite microspheres are nano-scale to micron-scale microspheres with rough surfaces; the porous hydroxyapatite microspheres have a nano-scale pore channel structure; the mineralization is improved under the assistance of the porous hydroxyapatite microspheres; the defects that hydroxyapatite microspheres in the prior art are sharp in microstructure, poor in histocompatibility, free of a porous structure and the like are overcome, the preparation method is simple, the safety coefficient of the production process is high, the obtained porous microspheres are stable in structure, various parameters can be adjusted according to requirements, and the method is suitable for industrial large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a highly stable porous hydroxyapatite microsphere and a preparation method and application thereof. Background Art

[0002] Hydroxyapatite (HAp) is one of the most common forms of calcium phosphate, with a chemical formula of Ca 10 (PO 4 ) 6 (OH) 2 , which is the main inorganic mineral component of human bones and teeth. Hydroxyapatite is also widely found in nature, such as the bones of vertebrates and the shells of mollusks. Hydroxyapatite has good biocompatibility and bioactivity. As an inorganic bone substitute material, it has been widely used in the medical field and has shown high application value in orthopedic surgery, maxillofacial surgery, drug controlled release and soft tissue filling and repair. However, since the hydroxyapatite crystal form belongs to the hexagonal system, P6 3 / m space group, the crystallographic parameters are a = 9.418 Å, c = 6.881 Å, β = 120°, so the smallest structural unit of hydroxyapatite prepared by traditional methods such as hydrothermal method is usually needle-shaped, which can easily stimulate the surrounding tissues to produce inflammatory responses after implantation in the body.

[0003] The preparation of calcium hydroxyphosphate into microspheres can improve the mechanical microenvironment when it contacts the surrounding tissues and reduce the probability of inflammatory response; the porous structure can increase the contact area between calcium hydroxyphosphate and body fluids after injection into the body, regulate its degradation rate to a certain extent, and facilitate the loading of drugs and stem cells. At present, the preparation methods of microspheres include hydrothermal method, spray drying method, sol-gel method, template method, etc.

[0004] For example, a Chinese patent (patent application number 202210911941.5) discloses a porous hydroxyapatite microsphere material and a method for preparing the same. However, its microstructure is a cluster of needle-shaped and lamellar hydroxyapatite calcium phosphate, which may produce a larger inflammatory response after injection. A Chinese patent (patent application number 202210364112.X) discloses hydroxyapatite microspheres and a method for preparing the same, but it does not have a porous structure, which is not conducive to loading drugs and regulating degradation time. A Chinese patent (patent application number 202310547230.9) discloses an injectable, high-purity medical hydroxyapatite microsphere and a method for preparing the same, which also does not have a porous structure.

[0005] Therefore, there is an urgent need for a highly stable porous hydroxyapatite microsphere and a preparation method and application thereof to solve the above problems. Summary of the invention

[0006] The purpose of the present invention is to provide a highly stable porous hydroxyapatite microsphere and a preparation method and application thereof.

[0007] The scheme of the present invention is: A highly stable porous hydroxyapatite microsphere, wherein the porous hydroxyapatite microsphere is formed by self-assembly of nano-scale hydroxyapatite particles driven by the thermodynamic behavior of reducing excess surface free energy; the porous hydroxyapatite microsphere is a nano-scale to micro-scale microsphere with a rough surface; and the porous hydroxyapatite microsphere has a nano-scale pore structure.

[0008] As a preferred technical solution, porous hydroxyapatite microspheres assist in improving mineralization, the nanoscale hydroxyapatite particles have a particle size range of 5 to 60 nm, and an aspect ratio range of 5:1 to 1:1; the nanoscale hydroxyapatite particles are combined by soft agglomeration or hard agglomeration to form the porous hydroxyapatite microspheres.

[0009] As a preferred technical solution, the porous hydroxyapatite microspheres are spherical or ellipsoidal in shape; the porous hydroxyapatite microspheres have a particle size range of 300nm to 150μm; the porous hydroxyapatite microspheres have any one or a combination of cross-linked holes, through holes or blind holes in their structure; The average pore size of the porous hydroxyapatite microsphere structure is 0.1 nm to 150 nm, the porosity is 0.1% to 90%, and the specific surface area is 100 to 0.06 m 2 / g.

[0010] The present invention also discloses a method for preparing highly stable porous hydroxyapatite microspheres, comprising the following steps: 1) dissolving phosphate in purified water and adjusting the pH to alkaline to obtain solution A; 2) Dissolve the calcium salt in purified water to obtain solution B; 3) Mix solution A and solution B under stirring and adjust the pH to 8.0-11.0 until the reaction is complete; 4) After the reaction is completed, stirring is stopped, and the supernatant is filtered out after natural sedimentation. Deionized water and ethanol are added to wash repeatedly to remove impurities. After filtering and drying, the crude hydroxyapatite product is obtained; 5) The crude hydroxyapatite product is crushed and dispersed into ultrafine hydroxyapatite powder; the obtained ultrafine hydroxyapatite powder is granulated and calcined to obtain porous hydroxyapatite microspheres.

[0011] As a preferred technical solution, the phosphate in step 1) is one of diammonium hydrogen phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, ammonium dihydrogen phosphate, sodium dihydrogen phosphate and potassium dihydrogen phosphate; and the concentration of solution A is 0.5-2.0 mol / L.

[0012] As a preferred technical solution, the phosphate is diammonium hydrogen phosphate, and the concentration of solution A is 1.0 mol / L.

[0013] As a preferred technical solution, the calcium salt in step 2) is one of calcium chloride, calcium bromide, calcium nitrate and dicalcium phosphate; and the concentration of solution B is 0.5-2.0 mol / L.

[0014] As a preferred technical solution, the calcium salt in step 2) is calcium nitrate; and the concentration of solution B is 1.0 mol / L.

[0015] As a preferred technical solution, in the step 3), the volume ratio of solution A to solution B when mixed is 1.6-1.8:1; the stirring paddle speed under the stirring conditions is set to 200 rpm-700 rpm; the pH is adjusted to 8.5; and the reaction time is 12-48 h.

[0016] As a preferred technical solution, in the step 3), the volume ratio of solution A and solution B when mixed is 1.67:1; the stirring paddle speed under the stirring condition is set to 300 rpm; the pH is adjusted to 8.5; and the reaction time is 24 h.

[0017] As a preferred technical solution, the pH regulator used in step 3) is one of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, and ammonia water. As a further optimization, the pH regulator used is ammonia water.

[0018] As a preferred technical solution, the washing method in the step 4) is to use purified water to wash until the pH of the filtrate is 7 and then use anhydrous ethanol to wash, and the number of times of anhydrous ethanol is ≥3; the filtering method is to use a microporous filter membrane to filter under reduced pressure, and the pore size of the filter membrane is 0.22μm to 0.45μm.

[0019] As a preferred technical solution, the number of times of anhydrous ethanol is 3 times; the filtering method is vacuum filtration using a microporous filter membrane, and the pore size of the filter membrane is 0.22 μm.

[0020] As a preferred technical solution, the drying method in step 4) is to dry in a vacuum oven above 80°C to constant weight. As a further optimization, at a temperature of 90°C and a pressure of 1.0×10 -3 MPa in a vacuum oven to dry to constant weight.

[0021] As a preferred technical solution, the method used for crushing and dispersing the crude hydroxyapatite product in step 5) is a combination of one or more methods of mechanical dispersion, ultrasonic dispersion and high-energy treatment; The mechanical dispersion is one of a roller method, a grinding method, a ball mill method, a vibration ball mill method, and an air mill method; The high energy treatment method is one of corona, ultraviolet light, microwave and plasma ray.

[0022] As a further optimization, in the step 5), the hydroxyapatite crude product is crushed and dispersed by vibration ball milling and corona, and the vibration ball mill speed is set to 2800 r / min, the ball milling time is 6 h, and the feed amount is 70% of the rated capacity. After the vibration ball milling, the ball milled powder is treated with a corona machine for 30 min to prevent the ultrafine nano hydroxyapatite powder from agglomerating.

[0023] The granulation method can be selected from one of drum granulation, vibration granulation, centrifugal granulation, fluidized granulation, extrusion granulation, spray granulation and freezing granulation; as a further optimization, the granulation method is centrifugal granulation; The granulation process is performed by adding a pore-forming agent; the pore-forming agent is one of ammonium bicarbonate, sodium bicarbonate, hydrogen peroxide, sodium chloride, potassium chloride, Pluronic, microcrystalline cellulose, and fatty acid salts. As a further optimization, the pore-forming agent is hydrogen peroxide. The burning temperature is 200-1000°C, and the burning time is 2h-24h.

[0024] As a preferred technical solution, the burning temperature is 400°C and the burning time is 6 hours.

[0025] The invention also discloses an application of nanoparticle self-assembled porous hydroxyapatite microspheres in assisting mineralization, bone tissue repair and filling, drug sustained-release carriers or tissue engineering scaffolds.

[0026] As a preferred technical solution, nanoparticle self-assembled porous hydroxyapatite microspheres have good adsorption capacity and are used as adsorbents, thereby being applied in related fields of use.

[0027] Due to the use of a highly stable porous hydroxyapatite microsphere and its preparation method and application, the porous hydroxyapatite microsphere is formed by self-assembly of nano-scale hydroxyapatite particles driven by the thermodynamic behavior of reducing excess surface free energy; the porous hydroxyapatite microsphere is a nano-scale to micron-scale microsphere with a rough surface; the porous hydroxyapatite microsphere has a nano-scale pore structure; the porous hydroxyapatite microsphere assists in improving mineralization.

[0028] Compared with the prior art, the present invention has the following beneficial effects: The present invention overcomes the defects of the hydroxyapatite microspheres in the prior art, such as relatively sharp microstructure, relatively poor tissue compatibility, and lack of porous structure. The preparation method of the present invention is simple, the production process has a high safety factor, the obtained porous microspheres have a stable structure, and various parameters can be adjusted according to needs, and are suitable for industrial scale-up production.

[0029] The advantages of the present invention are: (1) The preparation process of the present invention is simple and the reaction conditions are easy to control; (2) The hydroxyapatite microspheres prepared by the present invention have a porous structure, and porous microspheres with different particle sizes and porosities can be obtained by adjusting the production process parameters, thereby further realizing the regulation of the degradation rate of the microspheres, and having high stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a scanning electron microscope image of the hydroxyapatite microspheres obtained in Example 1 of the present invention; Figure 2 This is a scanning electron microscope image of the hydroxyapatite crude product obtained in Example 1 of the present invention, which is crushed into ultrafine powder. DETAILED DESCRIPTION

[0031] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0032] Example 1 Highly stable porous hydroxyapatite microspheres: 1) Weigh 79.2 g of diammonium hydrogen phosphate and dissolve it in 600 mL of water to obtain a 1.0 mol / L diammonium hydrogen phosphate aqueous solution. Add ammonia water and adjust the pH to 8.5 before use.

[0033] 2) Weigh 236 g of calcium nitrate tetrahydrate and dissolve it in 1000 mL of water to obtain a 1.0 mol / L calcium nitrate aqueous solution for later use.

[0034] 3) The diammonium hydrogen phosphate aqueous solution is transferred to the reactor, and the calcium nitrate aqueous solution is added dropwise to the diammonium hydrogen phosphate aqueous solution under stirring, and ammonia water is added to adjust the pH of the mixed solution to 8.5.

[0035] 4) After 24 hours of reaction, use a 0.22 μm microporous filter to filter out excess solvent, add deionized water for washing, and repeat the filtration step until the filtrate is neutral. Add ethanol and wash three times, then use a microporous filter to filter out excess ethanol. The filter residue is the crude hydroxyapatite product.

[0036] 5) Place the crude hydroxyapatite product at 90 °C, 1.0×10 -3 MPa in a vacuum oven to dry to constant weight.

[0037] 6) The dried hydroxyapatite crude product is placed in a vibration ball mill with a feed amount of 70% of the rated capacity. The vibration ball mill speed is set to 2800 r / min and the ball milling time is set to 6 h. After the vibration ball milling, the ball milled powder is treated with a corona machine for 30 minutes to prevent the ultrafine nano-hydroxyapatite powder from agglomerating.

[0038] 7) Transfer 100g ultrafine nano-hydroxyapatite powder into the centrifugal granulator, add 20g hydrogen peroxide, and set the speed to 3×10 4 r / min, blast speed is 1.5 m 3 / min, atomization pressure 1.5 MPa, granulation time 6 h. After granulation, the hydroxyapatite microspheres were transferred to a 400 ℃ muffle furnace and calcined for 6 h to obtain porous hydroxyapatite microspheres.

[0039] The average particle size of the microspheres was 25.4 μm, as measured by Beckman Counter. The porosity of the microspheres was 2%, the average pore size was 14.9 nm, and the specific surface area was 0.37 m 2 / g.

[0040] Example 2 Highly stable porous hydroxyapatite microspheres: 1) Weigh 39.6 g of diammonium hydrogen phosphate and dissolve it in 300 mL of water to obtain a 1.0 mol / L diammonium hydrogen phosphate aqueous solution. Add ammonia water and adjust the pH to 8.5 before use.

[0041] 2) Weigh 118 g of calcium nitrate tetrahydrate and dissolve it in 500 mL of water to obtain a 1.0 mol / L calcium nitrate aqueous solution for later use.

[0042] 3) The diammonium hydrogen phosphate aqueous solution is transferred to the reactor, and the calcium nitrate aqueous solution is added dropwise to the diammonium hydrogen phosphate aqueous solution under stirring, and ammonia water is added to adjust the pH of the mixed solution to 8.5.

[0043] 4) After 24 hours of reaction, use a 0.22 μm microporous filter to filter out excess solvent, add deionized water for washing, and repeat the filtration step until the filtrate is neutral. Add ethanol and wash three times, then use a microporous filter to filter out excess ethanol, and the filter residue is the crude hydroxyapatite product.

[0044] 5) The crude hydroxyapatite was placed at 90 °C, 1.0 × 10 -3 MPa in a vacuum oven to dry to constant weight.

[0045] 6) The dried hydroxyapatite crude product is placed in a vibration ball mill with a feed amount of 70% of the rated capacity. The vibration ball mill speed is set to 2800 r / min and the ball milling time is set to 6 h. After the vibration ball milling, the ball milled powder is treated with a corona machine for 30 minutes to prevent the ultrafine nano-hydroxyapatite powder from agglomerating.

[0046] 4) Transfer 100 g of ultrafine nano-hydroxyapatite powder into a centrifugal granulator and add 30 g of ammonium bicarbonate. Set the speed to 3×10 4 r / min, blast speed is 1.5 m 3 / min, atomization pressure 1.5 MPa, granulation time 6 h. After granulation, the hydroxyapatite microspheres were transferred to a 400 ℃ muffle furnace and calcined for 6 h to obtain porous hydroxyapatite microspheres.

[0047] The average particle size of the microspheres was 28.9 μm, as measured by Beckman Counter. The porosity of the microspheres was 27%, the average pore size was 121.5 nm, and the specific surface area was 0.65 m 2 / g.

[0048] Example 3 Highly stable porous hydroxyapatite microspheres: 1) Weigh 396 g of diammonium hydrogen phosphate and dissolve it in 3000 mL of water to obtain a diammonium hydrogen phosphate aqueous solution with a concentration of 1.0 mol / L. Add ammonia water and adjust the pH to 8.5 for later use.

[0049] 2) Weigh 1180 g of calcium nitrate tetrahydrate and dissolve it in 5000 mL of water to obtain a 1.0 mol / L calcium nitrate aqueous solution for later use.

[0050] 3) The diammonium hydrogen phosphate aqueous solution was transferred to a reaction kettle, and the calcium nitrate aqueous solution was added dropwise to the diammonium hydrogen phosphate aqueous solution under stirring, and ammonia water was added to adjust the pH of the mixed solution to 8.5.

[0051] 4) After 24 hours of reaction, use a 0.22 μm microporous filter to filter out excess solvent, add deionized water for washing, and repeat the filtration step until the filtrate is neutral. Add ethanol and wash three times, then use a microporous filter to filter out excess ethanol, and the filter residue is the crude hydroxyapatite product.

[0052] 5) The crude hydroxyapatite was placed at 90 °C, 1.0 × 10 -3 MPa in a vacuum oven to dry to constant weight.

[0053] 6) The dried hydroxyapatite crude product is placed in a vibration ball mill with a feed amount of 70% of the rated capacity. The vibration ball mill speed is set to 2800 r / min and the ball milling time is set to 6 h. After the vibration ball milling, the ball milled powder is treated with a corona machine for 30 minutes to prevent the ultrafine nano-hydroxyapatite powder from agglomerating.

[0054] 7) Transfer 100 g of ultrafine nano-hydroxyapatite powder into a centrifugal granulator and add 20 g of ammonium bicarbonate. Set the speed to 3×10 4 r / min, blast speed is 1.5 m 3 / min, atomization pressure 1.5 MPa, granulation time 12 h. After granulation, the hydroxyapatite microspheres were transferred to a 400 ℃ muffle furnace and calcined for 6 h to obtain porous hydroxyapatite microspheres.

[0055] The average particle size of the microspheres was 66.3 μm, as measured by Beckman Counter. The porosity of the microspheres was 19%, the average pore size was 77.9 nm, and the specific surface area was 0.46 m 2 / g.

[0056] Example 4 Highly stable porous hydroxyapatite microspheres: 1) Weigh 99 g of diammonium hydrogen phosphate and dissolve it in 750 mL of water to obtain a diammonium hydrogen phosphate aqueous solution with a concentration of 1.0 mol / L. Add ammonia water and adjust the pH to 8.5 for later use.

[0057] 2) Weigh 295 g of calcium nitrate tetrahydrate and dissolve it in 1250 mL of water to obtain a 1.0 mol / L calcium nitrate aqueous solution for later use.

[0058] 3) The diammonium hydrogen phosphate aqueous solution is transferred to the reactor, and the calcium nitrate aqueous solution is added dropwise to the diammonium hydrogen phosphate aqueous solution under stirring, and ammonia water is added to adjust the pH of the mixed solution to 8.5.

[0059] 4) After 24 hours of reaction, use a 0.22 μm microporous filter to filter out excess solvent, add deionized water for washing, and repeat the filtration step until the filtrate is neutral. Add ethanol and wash three times, then use a microporous filter to filter out excess ethanol. The filter residue is the crude hydroxyapatite product.

[0060] 5) The crude hydroxyapatite was placed at 90 °C, 1.0 × 10 -3 MPa in a vacuum oven to dry to constant weight.

[0061] 6) The dried hydroxyapatite crude product is placed in a vibration ball mill with a feed amount of 70% of the rated capacity. The vibration ball mill speed is set to 2800 r / min and the ball milling time is set to 6 h. After the vibration ball milling, the ball milled powder is treated with a corona machine for 30 minutes to prevent the ultrafine nano-hydroxyapatite powder from agglomerating.

[0062] 7) Transfer 100 g of ultrafine nano-hydroxyapatite powder into a centrifugal granulator and add 20 g of ammonium bicarbonate. Set the speed to 3×10 4 r / min, blast speed is 1.5 m 3 / min, atomization pressure 1.5 MPa, granulation time 0.5 h. After granulation, the hydroxyapatite microspheres were transferred to a 400 ℃ muffle furnace and calcined for 6 h to obtain porous hydroxyapatite microspheres.

[0063] The average particle size of the microspheres was 750 nm, which was determined by Beckman Counter. The porosity of the microspheres was 18%, the average pore size was 49.2 nm, and the specific surface area was 0.41 m 2 / g.

[0064] The highly stable porous hydroxyapatite microspheres in Example 1 were tested in a mineralization experiment: 1. Experimental testing 1.1 Preparation General data A total of 150 patients with deep caries from January 2012 to August 2024 were selected, with a total of 160 teeth. All the teeth were diagnosed by clinical exploration and X-ray examination. They were all young permanent teeth, including 73 males and 77 females, aged 9 to 13 years old; 7 cases of deep caries on bilateral mandibular first molars, 3 cases of deep caries on bilateral mandibular first molars and right maxillary first molars. The 120 teeth were randomly divided into clove oil group, 5% porous hydroxyapatite microsphere group, 10% porous hydroxyapatite microsphere group, and calcium hydroxide group, with 40 teeth in each group. There was no significant difference among the three groups, and they were comparable.

[0065] 1.2 Materials The highly stable porous hydroxyapatite microspheres prepared in Example 1 contain 5% highly stable porous hydroxyapatite microsphere group = calcium hydroxide paste + 5% highly stable porous hydroxyapatite microspheres accounting for the total mass of calcium hydroxide paste; The group containing 10% porous hydroxyapatite microspheres = calcium hydroxide paste + porous hydroxyapatite microspheres accounting for 10% of the total mass of calcium hydroxide paste; Calcium hydroxide paste is produced by Dandong Kangning Pharmaceutical Company, Liaoweixiaozhengzi (2004) No. 0078.

[0066] Zinc oxide eugenol cement is produced by the Dental Materials Factory of Shanghai Medical Instrument Co., Ltd., with the National Food and Drug Administration (Approved) No. 3630216 of 2006, and adopts the standard YY0272-1995.

[0067] 1.3 Experimental methods The experiment was completed in two parts. The first time, when removing caries, the softened dentin near the pulp was not necessarily removed. After the pits and fissures were cleaned and dried, the bottom of the cavity was covered with a 5% high-stability porous hydroxyapatite microsphere group, and the bottom was cushioned with zinc oxide clove oil cement powder and filled with zinc phosphate cement powder.

[0068] The cave bottom cover contains 10% highly stable porous hydroxyapatite microspheres, with zinc oxide clove oil cement as the base and zinc phosphate cement as the filling.

[0069] The clove oil group was directly cushioned with zinc oxide clove oil cement and filled with zinc phosphate cement.

[0070] The bottom of the hole is covered with a calcium hydroxide group, which is a calcium hydroxide paste, with zinc oxide clove oil cement powder as the base and zinc phosphate cement powder as the filling.

[0071] After 10 to 12 weeks, the experiment was repeated, all fillings were removed, and the remaining softened dentin was removed with a spoon. If there was no exposed pulp, indirect pulp capping, padding and permanent restoration were performed. X-rays were taken before and after for reference.

[0072] 1.4 Evaluation criteria After the experiment, there was no spontaneous pain, pain from hot or cold stimulation, no pain when biting. Clinical examination showed no pain from stimulation, looseness, percussion pain or sinus tract. During the follow-up visit, the initial light brown moist dentin had turned into gray or dark brown dry dentin. Comparison of the before and after X-rays showed remineralization of the softened dentin, which was successful. After treatment, pain from hot or cold stimulation, spontaneous pain and pain when biting occurred. Clinical examination showed looseness of the affected teeth, periodontal pockets, sinus tracts or abscess formation. The occurrence of any one of these items was considered a failure.

[0073] 2. Results The comparison experiment was performed after 12 weeks of follow-up observation. The results are shown in Table 1.

[0074] Table 1 Comparison of three groups of experiments Table 1 shows that the calcium hydroxide group has better efficacy than the clove oil group, and the group containing highly stable porous hydroxyapatite microspheres is better than the calcium hydroxide group. This method is simple and easy to use, painless and acceptable, and can preserve the vital pulp of young permanent teeth to the greatest extent. It proves that highly stable porous hydroxyapatite microspheres can be remineralized.

[0075] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A highly stable porous hydroxyapatite microsphere, characterized in that: The porous hydroxyapatite microspheres are formed by self-assembly of nano-sized hydroxyapatite particles driven by the thermodynamic behavior of excess surface free energy reduction; the porous hydroxyapatite microspheres are nano-sized to micro-sized microspheres with rough surfaces; and the porous hydroxyapatite microspheres have a nano-sized pore structure.

2. The highly stable porous hydroxyapatite microspheres according to claim 1, characterized in that: Porous hydroxyapatite microspheres assist in improving mineralization. The nano-scale hydroxyapatite particles have a particle size range of 5 to 60 nm and an aspect ratio range of 5:1 to 1:

1. The nano-scale hydroxyapatite particles are combined through soft agglomeration or hard agglomeration to form the porous hydroxyapatite microspheres.

3. The highly stable porous hydroxyapatite microspheres according to claim 1, characterized in that: The porous hydroxyapatite microspheres are spherical or ellipsoidal in shape; the particle size of the porous hydroxyapatite microspheres ranges from 300 nm to 150 μm; the porous hydroxyapatite microspheres have any one or a combination of cross-linked holes, through holes or blind holes in their structure; The average pore size of the porous hydroxyapatite microsphere structure is 0.1 nm to 150 nm, the porosity is 0.1% to 90%, and the specific surface area is 100 to 0.06 m 2 / g.

4. A method for preparing porous hydroxyapatite microspheres with high stability as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: 1) dissolving phosphate in purified water and adjusting the pH to alkaline to obtain solution A; 2) Dissolve the calcium salt in purified water to obtain solution B; 3) Mix solution A and solution B under stirring and adjust the pH to 8.0-11.0 until the reaction is complete; 4) After the reaction is completed, stirring is stopped, and the supernatant is filtered out after natural sedimentation. Deionized water and ethanol are added to wash repeatedly to remove impurities. After filtering and drying, the crude hydroxyapatite product is obtained; 5) The crude hydroxyapatite product is crushed and dispersed into ultrafine hydroxyapatite powder; the obtained ultrafine hydroxyapatite powder is granulated and calcined to obtain porous hydroxyapatite microspheres.

5. The method for preparing porous hydroxyapatite microspheres with high stability as claimed in claim 4, characterized in that: In the step 1), the phosphate is one of diammonium hydrogen phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, ammonium dihydrogen phosphate, sodium dihydrogen phosphate and potassium dihydrogen phosphate; and the concentration of solution A is 0.5-2.0 mol / L.

6. The method for preparing highly stable porous hydroxyapatite microspheres according to claim 4, characterized in that: In the step 2), the calcium salt is one of calcium chloride, calcium bromide, calcium nitrate and dicalcium phosphate; and the concentration of the solution B is 0.5-2.0 mol / L.

7. The method for preparing highly stable porous hydroxyapatite microspheres according to claim 4, characterized in that: In the step 3), the volume ratio of solution A to solution B when mixed is 1.6 to 1.8:1; the stirring speed of the stirring paddle is set to 200 rpm to 700 rpm under the stirring conditions; the pH is adjusted to 8.5; and the reaction time is 12 to 48 h.

8. The method for preparing highly stable porous hydroxyapatite microspheres according to claim 4, characterized in that: The washing method in the step 4) is to use purified water to wash until the pH of the filtrate is 7 and then use anhydrous ethanol to wash, and the number of times of anhydrous ethanol is ≥3; the filtering method is to use a microporous filter membrane to filter under reduced pressure, and the pore size of the filter membrane is 0.22μm to 0.45μm.

9. The method for preparing highly stable porous hydroxyapatite microspheres according to claim 4, characterized in that: In the step 5), the method for crushing and dispersing the crude hydroxyapatite product is a combination of one or more methods of mechanical dispersion, ultrasonic dispersion and high-energy treatment; The granulation method can be selected from one of drum granulation, vibration granulation, centrifugal granulation, fluidized granulation, extrusion granulation, spray granulation and freezing granulation; In the granulation process, a porogen is optionally added; The burning temperature is 200-1000°C, and the burning time is 2h-24h.

10. Use of the highly stable porous hydroxyapatite microspheres according to any one of claims 1 to 9 in assisting mineralization, bone tissue repair and filling, drug sustained-release carriers or tissue engineering scaffolds.

Citation Information

Patent Citations

  • Hydroxyapatite microspheres and preparation method thereof

    CN114890398A

  • A porous hydroxyapatite microsphere material and its preparation method

    CN115108542B

  • Injectable high-purity medical hydroxyapatite microsphere and preparation method thereof

    CN116946993A

Cited By

  • Biomass self-assembled porous microspheres regulated and controlled by carboxymethyl cellulose as well as preparation method and application of biomass self-assembled porous microspheres

    CN120478301A

  • Hydroxyapatite microspheres for skin injection filling and preparation method thereof

    CN120622429A

  • Hydroxyapatite microspheres for dermal injection and method for preparing the same

    CN120622429B